Analysis of Factors Affecting Customer Satisfaction Using Eucalyptus Oil on Walbarua Kettle in Ubung Village - Firman Gazali Djunaidi; R.S. Masna Hatuwe; A. Yusdianti Tenriawali; Heny Irnayanti Umagapy; M Chairul Basrun Umanailo (Kawanua International Journal of Multicultural Studies, 2020)
This study aims to determine what factors influence consumer satisfaction in using eucalyptus oil in a Walbarua kettle in Ubung village, Buru Regency. This research is quantitative descriptive. The research is located in the kettle Walbarua in Ubung village. The research object is consumers having bought eucalyptus oil repeatedly in a Walbarua kettle in Ubung Village. The research period is a month from April to May 2020. The data collection techniques in this study are observation and questionnaires. Data analysis in this study using multiple linear regression analysis. The results showed that there was an effect of product quality on consumer satisfaction who had used eucalyptus oil in a Walbarua kettle in Ubung village of 41.9%, and there was an effect of price on consumer satisfaction who had used eucalyptus oil in a Walbarua kettle in Ubung village of 38.1 %. Therefore, the affordable eucalyptus oil price is one of the main factors to attract the attention of consumers for buying eucalyptus oil in Ubung Village.